Control surfaces in confined spaces : the optimisation of trailing edge tabs to reduce control surface hinge moments - Jaquet, Christopher Denis (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2010.